SEBARAN GANGGUAN NEUROPSIKIATRI PADA STAF MEDIK NEUROLOGI SELAMA PANDEMI COVID-19 - Rini Nindela; Yunni Diansari; Sri Handayani; Selly Marisdina; Bintang Arroyantri Prananjaya (PERDOSNI, 2020)
Introduction: Corona Virus Disease-2019 (COVID-19) is a new disease designated as a global pandemic by WHO after causing a large number of deaths in a short period of time in various parts of the world. The COVID-19 pandemic has not only caused physical impacts, but also mental fatigue on the community, especially health workers as the frontline in handling COVID-19. Aim: To determine the distribution of neuropsychiatric symptoms among neurological medical staff that have occurred since the COVID-19 pandemic. Methods: This research was a descriptive study with a cross-sectional approach, taking place from May to June 2020 and was conducted on neurological medical staff who were members of the PERDOSSI and students participating in the Neurology specialist education program. Data collection was carried out using a questionnaire, namely the Beck Anxiety Inventory to assess anxiety, the Beck Depression Inventory to assess depression, the Insomnia Severity Index to assess insomnia and a checklist of questions to assess headaches that were sent online.. Results: The data obtained in this study indicate that a total of 13.6% of neurological medical staff in this study experienced anxiety, 4.5% experienced depression, 6.1% experienced insomnia, and 24.2% experienced headaches suspected to be related to COVID-19. The severity of neuropsychiatric symptoms in this study ranged from mild to moderate, none of the subjects experienced severe symptoms. Generally the subjects with these complaints were women and they did not feel safe with the personal protective equipment/PPE used. Discussion: The distribution of neuropsychiatric disorders due to the COVID-19 pandemic among neurology medical staff in the PERDOSSI’s working area is still low. Keywords: COVID-19 pandemic, neuropsychiatric disorders, neurology medical staff